Role of Endoanal Ultrasound in The Assessment of Causes of Anal Pain in Correlation with MRI - Said El Azizi, Hatem Mohamed; Soliman, Alaa Sayed Mohammed; Elbarmelgi, Mohamed Yehia Ahmed Abdelaal; Saad Aly, Aya Mohamed (Journal of Neonatal Surgery, 2025)
Background: Anal pain is a frequent, non-specific symptom with diverse etiologies. Accurate imaging is critical for diagnosis and treatment planning. Endoanal ultrasound (EAUS) and magnetic resonance imaging (MRI) are commonly employed tools. Aim: This study aimed to compare the diagnostic performance of EAUS and MRI in evaluating causes of anal pain, particularly perianal fistulas. Methods: This prospective study, 30 patients presenting with anal pain were evaluated between March 2022 and November 2024. All patients underwent detailed history-taking, clinical examination, EAUS, and MRI fistulography. Diagnostic accuracy for identifying fistulous tracts, internal openings, and complications was assessed. MRI served as the reference standard, and EAUS results were compared using McNemar's test and diagnostic indices. Results: Among the 25 patients ultimately diagnosed with anal fistula, EAUS detected primary tracts in 80% compared to 96% by MRI. Sensitivity and specificity of EAUS for detecting primary tracts were 83.3% and 100%, respectively. EAUS identified internal openings in 72% of cases with a sensitivity of 93.3%. Detection of complications such as abscesses showed 87.5% sensitivity and 100% specificity. EAUS had limited value in evaluating high or complex fistulas. In rare non-fistulous causes such as anal cancer and proctalgia fugax, both EAUS and MRI provided complementary insights. Conclusion: EAUS offers high diagnostic accuracy in evaluating superficial anal pathologies and internal openings and is a valuable first-line, cost-effective imaging modality for anal pain, especially when MRI is contraindicated. However, MRI remains superior for detecting complex and high perianal fistulas